A Comparative Study Examining the Management of Bowen's Disease in the United Kingdom and Australia - G. L. Morley; J. H. Matthews; I. Verpetinske; G. A. Thom (Hindawi Limited, 2015)
Background and Aim. The optimum management of Bowen's Disease (BD) is undefined. A review of current practice is required to allow the development of best practice guidelines. Methods. All BD cases, diagnosed in one UK centre and one Australian centre over a year (1 July 2012-30 June 2013), were analysed retrospectively. Patients with BD were identified from histopathology reports and their medical records were analysed to collect demographic data, site of lesion, and treatment used. Results. The treatment of 155 lesions from the UK centre and 151 lesions from the Australian centre was analysed. At both centres BD was most frequently observed on the face: UK had 70 (45%) lesions and Australia had 83 (55%) lesions (P=0.08). The greatest number of lesions was managed by the plastic surgery department in the UK centre, 72 (46%), and the dermatology department in the Australian centre, 121 (80%). The most common therapy was surgical excision at both centres. Conclusions. In both UK and Australia, BD arises on sun-exposed sites and was most commonly treated with surgical excision despite a lack of robust evidence-based guidelines.